2020
DOI: 10.1021/acsphotonics.0c00779
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Ambient Temperature Control for Highly Reproducible Layered Perovskite Light-Emitting Diodes

Abstract: Achieving high reproducibility in materials properties of perovskites is critical to the reliable development of optoelectronic device applications such as photovoltaics and light-emitting diodes. However, it can be difficult to obtain reproducible and optimized performance from these materials, particularly for reduced-dimensional perovskites, because different 2D/quasi-2D perovskite layer numbers have similar formation energies. Here, we report that variations in the exact ambient temperature during solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 65 publications
0
22
1
Order By: Relevance
“…With the variation of the thickness of the emissive layer from 60 to 325 nm, we could demonstrate the maximum efficiency for 100 nm thick perovskite film with a current efficiency of 15.4 cd A −1 and an EQE of 4.3%, in agreement with recent reports with a similar emissive material. [ 21,24,27,28 ] The thickness of the emissive layer for this n = 3 quasi‐2D perovskites in the range of 100–170 nm is found to be optimal thickness with improved charge carrier balance. Furthermore, an increase in the emissive layer thickness results in a low EQE of around 1% due to charge carrier imbalance (Figure 4d).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…With the variation of the thickness of the emissive layer from 60 to 325 nm, we could demonstrate the maximum efficiency for 100 nm thick perovskite film with a current efficiency of 15.4 cd A −1 and an EQE of 4.3%, in agreement with recent reports with a similar emissive material. [ 21,24,27,28 ] The thickness of the emissive layer for this n = 3 quasi‐2D perovskites in the range of 100–170 nm is found to be optimal thickness with improved charge carrier balance. Furthermore, an increase in the emissive layer thickness results in a low EQE of around 1% due to charge carrier imbalance (Figure 4d).…”
Section: Resultsmentioning
confidence: 96%
“…A device with an emissive layer thickness of 100 nm has the highest LE value of ≈15.4 cd A −1 and an EQE of 4.3% (Figure 4 and Table 1 ), in agreement with recent reports for such systems. [ 21,24,27,28 ] Furthermore, an increase in an emissive layer thickness to 220 and 325 nm shows a decrease in EQE despite higher relative PL can be due to an imbalance of charge carriers. Hence, the thickness in the range of 100–170 nm seems to be optimal for n = 3 quasi‐2D perovskites (Figure 4a,b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This temperature is most commonly that found inside the glove box and can vary throughout the day and across seasons by around 10°C. In 2020, the group of Han et al [20] demonstrated that the performance of perovskite based light emitting diodes (LEDs) depended on the ambient temperature over a range of 21-31°C. These authors observed different crystallographic orientation of the Ruddlesden-Popper phase perovskites with the formula of PEA 2 MA n-1 Pb n Br 3n-1 whose formation depends on the temperature in the glovebox during the solution processing.…”
Section: Introductionmentioning
confidence: 99%